Rapid healing of venous ulcers with terminal, axial and perforator interruption of the reflux source (TAPIRS) plus multilayer bandage: A clinical trial (2016)
Introduction Chronic venous ulcers (CVU) are the most common ulcers occurring in the lower limbs, having a high morbidity and place a high financial strain on the health system. The traditional surgical techniques are being replaced by minimally invasive procedures, such as foam sclerotherapy. Objective The aim of this study was to determine CVU healing times and rates using the terminal, axial and perforator interruption of the reflux source (TAPIRS) protocol, which included an endoluminal venous occlusion with ultrasound-guided foam and a multilayer bandage system until achieving ulcer healing. Material and methods A prospective uncontrolled trial was conducted on patients with chronic venous leg ulcers (CEAP [clinical, etiological, anatomical and pathological elements] C6) during 2013 and 2014. A total of 17 patients aged 18 years and over, presenting with venous insufficiency, CVU, and an ankle-brachial index greater than 0.8, were included, and total of 17 limbs were analysed. All of the patients were subjected to endoluminal occlusion with ultrasound-guided foam in the axial superficial venous system and perforator and terminal veins near to the ulcer, using Tessari method with 3% polidocanol. Follow-up was carried out at every week and a doppler test was conducted after 4 and 12 weeks. Results The mean age of the patients was 56.4 years. The active ulcer duration prior to treatment was 2.96 years. The study showed that all CVU were healing before 7 weeks, the healing rate was 3.92 cm2/week, and the time until the ulcer was healed was 3.53 weeks (24 days). Conclusions The minimally invasive ablation of terminal, axial and perforator reflux with compression in patients is a technique that leads to faster healing times of CVU. © 2016 SEACV